Bonded by Interactions: Polarising Factors and Integrative Capacities of the News Media in Hungary - Bene, Marton; Szabó, Gabriella (Javnost-The Public, 2019)
The article addresses the issue of political polarisation in the news media in Hungary. Hungary is an illustrative case of a country which has been studied as the example of high political parallelism in news media, and one of the most politically polarised societies in Europe. We contribute to the literature in a number of ways. First, to our knowledge, this is a pioneering study in the application of network analysis to measuring political polarisation in the news media. Second, we provide evidence that fragmentation and heavy partisanship do not necessarily lead to extreme polarisation. The study presents an issue-centred and context-based approach to assessing whether mass communication channels form integrated or divided news media spaces for public discussion. For an empirical test, we explore the news media networks of three of the most widely covered issues of 2014. To link a medium to another one, we concentrate on interactions, which are defined as explicit citations or hyperlinks to the content of other media products and the communication of politicians. The findings support the claim of moderate polarisation in the Hungarian news media. Although ideologically divergent blocs are detected, there are intensive interactions between news media outlets of different political colours.